Tindak Tutur Ilokusi Dalam Bahasa Iklan Di Stasiun Televisi Nasional - Ritonga, Marta; Hermaliza, Hermaliza (J-LELC: Journal of Language Education, Linguistics, and Culture, 2022)
Illocutionary speech acts are used to say or inform something, and can also be used to do something. There are many utterances in advertisements on national television that contain illocutionary speech acts. The problem of this research is how illocutionary speech acts are used in advertising language on national televisi stations. This study aims to describe, analyze and interpret illocutionary speech acts in advertising language on national television stations. theory that the author uses theory Dewa Putu Wijana (1996) and Tarigan (2009:42). The method used in This description in the form of words sentences on food and beverage adservation stations using observation using observation, listening, note taking, documentation, and data analysis techniques. The results of this study indicate that the types of illocutionary speech acts in food and beverage advertisements on national televisi stations are assertive speech acts with a total of 48 uttterances, directive speech acts with a total of 4 utterances, commissive speech acts with a total of 5 utterances, expressive speech acts with a total of 4 utterances. The result from all data is 61 utterances.